Behavior of rural and urban free-ranging dogs in Viçosa, Minas Gerais, Brazil - Martinez, Edilberto; Cesário, Carice Silva [UNESP]; Ferraz, Fausto; Repolês, Renata; Silva, Ita Oliveira; Boere, Vanner (Elsevier, 2022)
Free-ranging dogs are often associated with human habitation in many developing countries, and are found in both rural and urban environments in Viçosa, Brazil. Urban free-ranging dogs (UFDs) are opportunistic and feed on leftovers, whether given to them or scavenged from trash cans while they wander about the streets. Most free-ranging dogs living in rural areas (RFDs) protect property and cattle. Depending on their behaviors, such as aggression or roaming, both UFDs and RFDs can be a health problem for people and other animals. The aim of this study was to investigate behavioral differences between UFDs and RFDs. Due to the guardian role of RFDs, it was hypothesized that they would be more aggressive and present less locomotor activity than the UFDs. In this study, 40 UFDs living on the Federal University of Viçosa (UFV) campus and 15 RFDs living on 6 rural properties in Viçosa, Brazil, were examined. The dogs were observed for twelve months, at different times during a 24-hour cycle, with 14 behavioral categories being recorded. RFDs showed significantly more vigilance (P< 0.01) and interspecific agonistic behavior (P< 0.01) than UFDs. UFDs showed significantly more locomotor behavior (P< 0.01) than RFDs. UFDs are less aggressive than RFDs, but they move more often. Resource availability, such as scattered food, influenced the locomotor activity in UFDs, whereas RFDs did not experience the same effect as they were supplied with a temporal and spatial feeding schedule. To the RFDs, concentrated resources such as food and shelter are highly defensible. This study showed that, in Viçosa (Brazil), RFDs and UFDs displayed different behaviors. These differences are most likely driven by the resource-defense behavior of RFDs.
Keywords: agonistic behavior; behavioral ecology; Canis lupus familiaris; locomotion; vigilance